The Essentials of Studies on IT and Management Accounting - Fitri Purnamasari; Sheila Febriani Putri; Nurul Azizah (AIBPM Publisher, 2019)
As computerized systems are increasingly being used including in every aspects, there are various interesting topics that can be taken and developed by subsequent researchers related to the phenomena. This paper seeks to help researchers by presenting summaries, quotations and comparisons of some studies related to the role and needs/urgency of information technology adaptation especially in management accounting area. The role and urgency of information technology in management accounting can be reviewed in various contexts; such as business and education contexts. Besides, the review process also can be carried out through research with various methods. Researchers need to design and map the objectives of the research to be taken clearly, then choose the appropriate method for realizing the goal.